Meningkatkan Maharah Kalam Siswa MTs Kelas VII Mambaus Sholihin Melalui Penggunaan Media Gambar - Farid Qomaruddin (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to improve the speaking skills of seventh-grade students at the Mamba’us Sholihin School through the implementation of the